Pre- and postoperative prognostic factors for resectable esophageal adenocarcinoma. (December 2020) - Serralheiro, Pedro; Rankin, Adeline; Clark, Allan; Holyoake, Daniel; Cheong, Edward
Abstract: Background: Prognostication for esophageal cancer has traditionally relied on postoperative tissue specimens. This study aimed to use a histologically homogenous cohort to investigate the relationship between clinical, pathological or radiological variables and overall survival in patients undergoing esophagectomy for adenocarcinoma. Methods: A single-centre study of patients who underwent esophagectomy for adenocarcinoma over 10 years in a tertiary centre was performed. By regression analysis, variables available preoperatively and postoperatively were studied for prognostication. The primary outcome was overall survival. Results: 254 cases were analyzed. Over a median follow-up period of 31.8 months (IQR = 42.5), overall survival was 51.5 months (95% confidence interval: 33.0–69.9). According to hazard ratios (HR) for all-cause death, adverse prognostic factors included: a higher postoperative N-stage (HR ≥ 1.29; p ≤ 0.024), histopathological tumor length ≥25 mm (HR = 2.04; p = 0.03), poorer tumor differentiation (HR ≥ 2.86; p ≤ 0.042), and R1 status (HR = 2.33; p = 0.02). A lymph node yield ≥35 was a favorable prognostic factor (HR = 0.022; p < 0.001). Demographic and radiological variables, preoperative TNM stages, postoperative T-stage, and neoadjuvant/adjuvant treatment were not associated with overall survival. Conclusions: This study identifies several postoperatively factors which are available for the prognostication and identifies factors that should not be used to exclude patients from curative surgery. Highlights: Single-centre study of 254 patients with esophageal adenocarcinoma. Pre and postoperatively variables models were studied for prognostication. Histopathological N-stage and tumor length were good prognostic factors. Age and preoperative radiological staging, were not associated with prognosis. Histopathological T-stage may be of less importance for prognostication.